Efektivitas Terapi Kelompok Game Activity terhadap Fungsi Kognitif pada Lansia - Aini, Endah Nur; Retna Febri Arifiati (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Elderly people experience various changes, one of which is cognitive changes due to shrinkage in the brain area, especially in the prefrontal cortex and hippocampus, which affect cognitive function and quality of life. Game activity group therapy is an effective non-pharmacological intervention to stimulate and slow down cognitive decline by training aspects of cognitive function such as attention, memory, language, visuospatial, calculation, and executive. Objectives: This study aims to determine the effect of game activity group therapy on the cognitive function of the elderly in Sawahan Kidul Hamlet, Ngemplak District, Boyolali Regency. Methods: Pre-experimental quantitative research with one group pretest-posttest design. The sampling technique used purposive sampling of 30 samples. The instrument used was MoCa-Ina. The hypothesis test used was paired sample t-test Results: The results of this study were dominated by elderly people aged 60-69 years as many as 24 samples (80%) and elderly women as many as 25 samples (83.3%). The pretest results showed an average score of 18.40 and the posttest results showed an average score of 21.17. The data normality test used Shapiro-Wilk with a p-value in the pre-test of 0.474 and a post-test of 0.897, indicating a p-value (> 0.05). Hypothesis testing using the paired t-test showed a p-value = 0.000. Conclusion: There is an influence of game activity group therapy on the cognitive function of the elderly in Sawahan Kidul Hamlet, Ngemplak District, Boyolali Regency. The results of this study are expected to be a choice of therapeutic activities to improve cognitive function in the elderly and individuals with cognitive disorders. Keywords: Elderly, Group Therapy, Game Activity, Cognitive Function